Safe Transitions for Every Patient (STEP): It's PRIMARY: Workshop for Residents in Care Transition Communication - Michael Weisgerber; Heather Toth; David Klehm; Geoffrey Lamb; Linda Meurer (Association of American Medical Colleges, 2011)
Abstract This resource contains the materials and instructor's guide for the highly rated Safe Transitions for Every Patient (STEP) resident workshop. Care transitions are a key component of good patient care, and poor communication is known to be a major contributor to patient harm. Few educational materials are available to train residents in this important skill. To address this gap, the STEP Collaborative, composed of faculty from internal medicine, family medicine, and pediatrics, systematically designed a resident-focused workshop on care transitions. This 1-hour workshop is composed of an introductory presentation, an interactive discussion of critical incidents involving care transitions, and a spirited Jeopardy-like game to reinforce key elements of the standardized care transition process. This workshop packet contains the PRIMARY care transition mnemonic, a critical incident worksheet, a quiz for assessing learner knowledge, and a workshop evaluation form. By using these materials, users can create a fun and valuable interactive care transition training experience for their residents that is easily adaptable to other audiences. Sixty-four family medicine, pediatric, and internal medicine residents attended and evaluated this 1-hour workshop. Eighty-seven percent gave this curriculum a high-pass rating. Resident reaction data were positive, with most mean ratings in the 5-6 range on a 7-point Likert Scale (with 7 = Excellent) in the areas of presenter knowledge, content relevance, material clarity, and the program's effects on learning.